Earned Value Management (EVM) Analysis for Maintenance Projects: Insights from GKB 4 at Universitas Muhammadiyah Malang - Wahyudiono, Sandi; Utari, Rini Pebri (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2025)
Building maintenance is a critical element of asset management to ensure functional feasibility, safety, and operational efficiency. This study evaluates the effectiveness of implementing Earned Value Management (EVM) in the maintenance project of Building 4, Universitas Muhammadiyah Malang (GKB 4 UMM), based on the Building Maintenance and Care Guidelines (Permen PU No. 24/PRT/M/2008). The research method includes collecting actual project data, analyzing EVM metrics such as Planned Value (PV), Earned Value (EV), and Actual Cost (AC), as well as calculating variance and performance indices. The results demonstrate that EVM effectively detects cost inefficiencies, with a total Cost Variance (CV) of Rp -70,012,501 and an average Cost Performance Index (CPI) of 0.88, highlighting low cost efficiency in key components such as brick walls and lifts. The project is on schedule with an average Schedule Performance Index (SPI) of 1.01. This study concludes that EVM serves as a reliable tool for identifying cost deviations, enabling quicker and more accurate evaluations, and supporting budget optimization for building maintenance projects.